2019
DOI: 10.33702/cmher.201901.1.2
|View full text |Cite
|
Sign up to set email alerts
|

Health Service Utilization and associated factors Among Older Adults in Ambo Town, West Shoa Zone, Oromia, Ethiopia

Abstract: In any country use of health services by elderly could vary according to the cultural, social, economic and demographic situation of the person who may need care. In certain contexts, it particularly varies with age and sex of the potential service user. However; there is paucity of information on the level and associated factors on health service utilization among elderly population in Ethiopia in general and in the study site in particular. To assess Factors Health Service Utilization and associated factors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…A further decline in health level leads to an increase in the burden of medical expenses, forming a vicious circle. Chinese and foreign scholars have confirmed through research on different regions of the world that economic difficulties are the primary reason why the poor population does not seek medical care 8 9. In addition, studies have shown that older adults’ perceptions of their own health status can also affect medical treatment behaviour.…”
Section: Introductionmentioning
confidence: 99%
“…A further decline in health level leads to an increase in the burden of medical expenses, forming a vicious circle. Chinese and foreign scholars have confirmed through research on different regions of the world that economic difficulties are the primary reason why the poor population does not seek medical care 8 9. In addition, studies have shown that older adults’ perceptions of their own health status can also affect medical treatment behaviour.…”
Section: Introductionmentioning
confidence: 99%